Mean platelet volume levels in patients with cardiac myxoma. (December 2014) - Kalkan, Mehmet Emin; Açar, Göksel; Şahin, Müslüm; Taş, Muhammed Hakan; Demir, Serdar; Yanartaş, Mehmed; Acar, Rezzan Deniz
Abstract Thromboembolic events such as cerebrovascular stroke are common and serious complications in patients with cardiac myxomas (CMs). Previous studies have reported that a high mean platelet volume (MPV) level reflects an activated platelet function and has been proven to be an independent risk factor for thromboembolic events. The aim of this study was to evaluate the relation between MPV level and CM. We compared the MPV levels between patients with CM and control subjects, and also evaluated the differences in the MPV levels in patients with CM before and after a successful surgical treatment. Furthermore, we compared the MPV levels in patients with and without cerebrovascular embolic symptoms. Fifty-one consecutive patients (13 men, 38 women, mean age 51.1 ± 16.9 years) who underwent excision of CM in our hospital in the last 13 years and 50 normal subjects as the control group were included in this study. The patients with CM were divided into two groups according to the presence or absence of cerebrovascular embolic symptoms. The preoperative and postoperative MPV levels of each CM patient was evaluated. MPV levels were found to be significantly higher in patients with CM than in control subjects (9.86 ± 1.30 fL vs. 7.63 ± 0.78 fL, p < 0.001). Moreover, the MPV levels significantly decreased after the surgical removal of CM (9.86 ± 1.30 fL vs. 8.68 ± 1.20 fL, p < 0.001). We also found that the MPV values were significantly higher in patients with neurological embolic events (10.55 ± 1.29 fL vs. 9.59 ± 0.78 fL, p = 0.016). We conclude that increased MPV levels might be considered as a marker of increased thromboembolic risk in patients with CM.